2019
DOI: 10.1111/ffe.13051
|View full text |Cite
|
Sign up to set email alerts
|

Stress state and stress‐induced microstructural evolution around the crack tip of G115 steel after dwell‐fatigue crack propagation

Abstract: Many components operate under creep‐fatigue loading causing an increasing need to learn the knowledge about creep‐fatigue crack growth (CFCG). The stress and microstructural evolution around the crack tip of G115 steel after CFCG were investigated. According to the finite element simulations, the variations of equivalent stress and stress triaxiality in the crack tip zone are presented. Furthermore, the evolutions of martensitic laths, dislocations, and precipitates were systematically studied through electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The reason why the authors chose these four lines was to understand the effects of SL on extended lines that are not collinear with the crack. For the crack propagation, the formation and coalescence of voids play an important role and always happen in the zone ahead of the crack tip instead of above the crack face 6,50,51 . Therefore, the effects of plastic strain for the zone above the crack face were not the research target, and the lines were not extended to the element above the crack face.…”
Section: Resultsmentioning
confidence: 99%
“…The reason why the authors chose these four lines was to understand the effects of SL on extended lines that are not collinear with the crack. For the crack propagation, the formation and coalescence of voids play an important role and always happen in the zone ahead of the crack tip instead of above the crack face 6,50,51 . Therefore, the effects of plastic strain for the zone above the crack face were not the research target, and the lines were not extended to the element above the crack face.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] Creep-fatigue interaction is a typical damage mode of turbine components, and attracts numerous attentions. [17][18][19][20] Wang et al 17 proposed a creep-fatigue life estimation model using the concept of the hysteresis energy density rate. Rai et al 18 experimentally investigated the creep-fatigue deformation micromechanisms of CM 247 DS LC alloy and suggested that the generation of dislocation substructures changed with the dwell times.…”
Section: Introductionmentioning
confidence: 99%
“…Creep‐fatigue interaction is a typical damage mode of turbine components, and attracts numerous attentions 17–20 . Wang et al 17 proposed a creep‐fatigue life estimation model using the concept of the hysteresis energy density rate.…”
Section: Introductionmentioning
confidence: 99%